Optimalization of Microsoft PowerPoint as a Civic Education Learning Media for Civic Education Junior High School Teachers in East Jakarta - Sarkadi, Sarkadi; Iasha, Vina (Opción, 2019)
This study aimed to develop the skills of Civic Education Junior High School Teachers in East Jakarta regarding the optimization of Microsoft PowerPoint as a learning media for Civic Education. This study used a research and devel- opment approach. Based on the results of this study concluded that MS Pow- erpoints developed learning media. in this study proved to be valid, practical, and could add to the skills of teachers in delivering Civic Education learning materials using technology in Era 4.0 in Junior High Schools (SMP) in East Jakarta.